Uma análise do diferencial competitivo de hotéis associados a cadeias hoteleiras internacionais - Castello Miguel, Isabela (2001)
The main purpose of this dissertation was to analyse whether hotels managed by international hotel chains present competitive differential when compared to hotels independently operated. This dissertation was only concerned with analyzing the benefits brought to the hotel, according to the marketing point of view, taking into consideration the differentials related to the brands, the distribution channels, the marketing budget and the commercial structure offered by the hotel chains to their affiliated hotels.This dissertation was developed through reading, as well as interviewing professionals of the area, such as hotels managers, hotel chains' directors, and consultant of hotel area in order to get to know their perceptions about the subject. Executive hotels under the luxury category were analyzed in the city of São Paulo.The conclusion was that hotels managed by international chains do present competitive differential in relation to the independently operated hotels. This differential is due to the usage of a brand known worldwide, the marketing budget, the sales and commercial structure of the hotels chains. This benefit is even bigger when the hotel is inside the international market.